MODELING THE EFFECT OF WHEELED TRACTORS AND SKIDDED TIMBER BUNCHES ON FOREST SOIL COMPACTION - Grigorev, Igor; Kunickaya, Olga; Burgonutdinov, Albert; Tikhonov, Evgeniy; Makuev, Valentin; Egipko, Sergey; Hertz, Edward; Zorin, Maksim (Journal of Applied Engineering Science, 2021)
An increasing demand for forest products incites a large number of log transportation operations, which may lead to negative consequences for the soil and the ecosystem as a whole. This paper is focused on establishing a mathematical model to estimate the soil deformation and compaction processes under tires of wheeled forest machines and individual components of the skidding system such as forwarder, limbs, butts, and tops of tree-lengths in high latitudes, permafrost soil and forests. The method applied is based on simulating the impact processes of elastic tires and the skidding system on the soil through a mathematical device for the measurement of the compaction parameters for different types of soil and the size of the shelterbelt. The effectiveness of the proposed models was evaluated according to experimental results. The influence of the rheological (elastic, viscous, and plastic) properties of soil were studied. The elasticity of tires and the running speed of forest machines can help to control the performance of forest machines. This can be done by reducing the pressure exerted on the soil and increasing the number of skidder passes 1.5-2-fold. Comparative analysis showed that the calculated data differ from the experimental ones by no more than 10%. The obtained results and the developed model will allow for a qualitative and quantitative assessment of technological impact on the soil during the projecting maps for logging operations.